The Relationship between Total Quality Management and Education Performance with Mediating Effects of Quality Assurance and Accreditation System in Pakistan Higher Education - Hashmi, Baqir Nadeem; Ahmad, Md Fauzi Bin (International Review of Management and Marketing, 2026)
Total quality management has received significant attention in the last few decades, with its applicability expanding across various industries, including higher education, to improve quality processes. Drawing on contingency and social theory, this research examines the mediating role of the quality assurance and accreditation system in the relationship between total quality management and the educational performance of higher education institutions in Pakistan. To attain the objectives, a close-ended, structured questionnaire was distributed via self-administration and emailed to 600 top management members of higher education institutions, selected through convenience sampling from the total population of 1291. To analyse the data and test the hypothesis, the partial least squares structural equation modeling technique was employed using the bootstrap method. The empirical result revealed that TQM is positively associated with the educational performance of higher education institutions in Pakistan. Furthermore, the quality assurance and accreditation system is positively correlated with the educational performance of higher education institutions in Pakistan. Moreover, quality assurance and accreditation both mediate the relationship between TQM and educational performance. Lastly, quality assurance was also found to be positively related to the accreditation system in higher education institutions in Pakistan. The study contributes to the existing literature by developing a pathway grounded in accreditation and quality assurance to improve educational performance.